ESRA19-0455 Variations in distance from skin to epidural space in children. (30th August 2019) - Wong, J; Lim, S
Abstract : Background and aims: Insertion of epidural catheters may be technically challenging due to variations in age and weight within the paediatric population. We studied the skin-to-epidural distance in both thoracic and lumbar regions to determine the relationship between age, weight and the depth to the epidural space in our Singapore paediatric population. Methods: Data from the Acute Pain Service was prospectively collected over 16 years. Details included patient demographics, level of epidural performed and distance from skin to epidural space. Regression analysis was performed to predict the depth to both thoracic and lumbar epidural spaces based on age and body weight. Results: A total of 616 midline epidurals were studied. Our study revealed a correlation between skin-to-epidural distance and both age and weight in children. the best correlation was demonstrated between skin-to-lumbar epidural distance and body weight (R2 = 0.743). Conclusions: Skin-to-lumbar epidural distance correlated with age and weight in children. Our results highlighted the differences between Southeast Asian paediatric populations when compared to other populations.